Estimating disease prevalence in large datasets using genetic risk scores - Benjamin D. Evans (Nature Portfolio, 2021)
Estimating disease prevalence in biobanks is prone to error, especially for self-reported traits. Here, the authors propose a method to estimate the prevalence of a disease within a cohort based on genetic risk scores.